Capoeira escolar : a arte popular para uma educação ético-estética - Placedino, Fernando Campiol (2014)
The research aims to, at a pedagogical and philosophical approach, understand the meaning(s) of Capoeira School Lessons in the first years of elementary school, understanding the possibilities for its contributions to an ethic-aesthetic education. In this way, Capoeira is understood as a Brazilian folk art, which has its historicity and cultural qualities, besides its potential as an aesthetic experience. Consisting of multiple strategies, the Fighting-Art finds in the perceptual body, that which reconnects in a complementing way, not only the singularities of the universe of Capoeira, but sensations that can incite the understanding and manifestations related to relevant concepts and postures pertaining to the execution of universal ethical attitudes, such as the recognition of plurality and otherness. This investigative path was supported from a phenomenological perspective reconnected to Education by Antonio Muniz de Rezende. Allied to this, the technique of bricolage was used, considering and reconciling various available research tools, such as participatory field observations, records of accounts, semi-structured interviews, and interpretation of discourses, as well as insights into theoretical support from Friedrich Schiller, Hans-Georg Gadamer, Jürgen Habermas, Merleau-Ponty, Muleka Mwewa, Nadja Hermann, Richard Shusterman, Zygmunt Bauman, and others. Therefore, such entanglements between knowledge, aesthetic perceptions and aspects of morality collaborate to enhance the important relations between education, aesthetics, and ethics, which still remain displaced in the pedagogical discussions in schools.